This preview shows page 1. Sign up to view the full content.
Unformatted text preview: tep 2.
For example in case of function Fi of Figure 6.17, the following five combinations of the
variables produce a 0:
000, 010,011, 101, and 110
Their corresponding maxterms are:
(x + y + z), (x + y + z), (x + y + z), (x + y + z), and (x + y + z)
Hence, taking the product (AND) of all these maxterms, the function Fi can be expressed
in its product-of-sums form as:
F1 = (x + y + z) • (x + y + z) • (x + y + z) • (x + y + z) • (x + y + z)
Similarly, it may be easily verified that the function F 2 of Figure 6.17 can be expressed in
its product-of-sums form as:
F2 = (x + y + z)-(x + y + z) • (x + y + z) • (x + y + z) or
F2 = M0 • M, • M2 • M4
In order to express a Boolean function in its product-of-sums form, it must first be
brought into a form of OR terms. This may be done by using the distributive laws:
x + y • z = (x + y) • (x + z)
Then any missing variable (say x) in each OR term is ORed with the form x • x. This
procedure is explained with the following example.
Express the Boolean function F = x • y + x • z in the product-of-maxterms (sums) form.
At first we convert the function into OR terms using the distributive law:
= (x • y + x) • (x • y + z)
= (x+x) • (y+x) • (x + z) • (y + z) = (x+y) • (x + z) • (y + z)
The function has three variables x, y and z. Each OR term is missing one variable,
x +y = x +y + Z • Z = (x +y + Z) • (X +y+ Z)
x + z = x + z +"-y • y =(x + z + y) • (x + z+ y) = (x +y + z)-(x + y +z) y + z
= x • +y + z = (x + y + z)-(x+y + z)
Combining all the terms and removing those that appear more than once, we finally
F = (x + y + z) • (x + y + z) • (x + y + z) • (x + y+ z) = M0 • M2 • M4 • M5
A convenient way to express this function is as follows:
F (x, y, z) = II (0, 2, 4, 5)
The product symbol FI denotes the ANDing of maxterms. The numbers following it are
the maxterms of the function.
The sum-of-products and the product-of-sums form of Boolean expressions are known as
standard forms. One prime reason for liking the sum-of-products or the product-of-sums
expressions is their...
View Full Document
- Spring '14